Not A Joke: Clown Archetypes Of Joker As Potrayed By Nicholson, Ledger, Leto, And Phoenix - Arya Saputra; Akmalia Fadhilah; Syahrifatus Zaroh Nabella Wardani; Inggita Lisda Mayasari; Della Amalia Putri; Rahma Kumala Tsani; Lusiana Pratiwi (Nusantara Journal of Multidisciplinary Science, 2023)
The Joker is an antagonist known for his flashy appearance as well as his crazy, cunning, manipulative, and sadistic nature. Changes in the clown archetype from The Joker character according to the comic version to various film adaptations, played by four different actors is understudied. The study uses qualitative techniques aimed at exploring and investigating the phenomenon and how these adaptations are carried out. This research used Bala clown archetype theory used to analyze clown self-journey, Hutcheon adaptation used to analyze clown archetype changes, and Witch and clown theory from Ann Belford Ulanov used to analyze clown sexuality. Using that theory, we find changes in the Joker clown archetype, namely The Fool, The Jester, and The Trickster, in various adaptations when starring Jack Nicholson, Heath Ledger, Jared Leto and Joaquin Phoenix. This study can be used as a guide by adaptation practitioners to show how the portrayal of the clown archetype Joker changes from the comic book version to the film version played by a different actor.